1998
DOI: 10.1093/oxfordjournals.molbev.a026005
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of satellite DNAs from the genus Palorus--experimental evidence for the "library" hypothesis

Abstract: Satellite DNA profiles have been characterized in the congeneric species Palorus ratzeburgii, Palorus subdepressus, Palorus genalis, and Palorus ficicola (Coleoptera, Insecta), each of which contains a single, AϩT-rich satellite DNA comprising a considerable portion of the genome (20%-40%). These satellites exhibit insignificant mutual sequence similarity. Using PCR assay, it has been shown that all four sequences are present in each of the tested Palorus species: one of them is amplified into a high copy numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
103
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 29 publications
11
103
0
Order By: Relevance
“…Their position within the variability profile of other monomers indicates a recent origin by amplification of a variant from a common pool, probably in the course or after speciation. This distribution is consistent with the satDNA library model (Fry and Salser, 1977;Meštrović et al, 1998Meštrović et al, , 2006a, but with monomer variants acting as independent amplification-contraction units. Their random amplification in the library (Pons et al, 2004) can explain the dominance of a homogeneous cluster of monomers in M. arenaria, the abundance of divergent variants lacking species specificity, or the combination of both features in V. decussata and V. rhomboides, respectively.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Their position within the variability profile of other monomers indicates a recent origin by amplification of a variant from a common pool, probably in the course or after speciation. This distribution is consistent with the satDNA library model (Fry and Salser, 1977;Meštrović et al, 1998Meštrović et al, , 2006a, but with monomer variants acting as independent amplification-contraction units. Their random amplification in the library (Pons et al, 2004) can explain the dominance of a homogeneous cluster of monomers in M. arenaria, the abundance of divergent variants lacking species specificity, or the combination of both features in V. decussata and V. rhomboides, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Source arrays (Figure 5c) and those formed by mutated monomers (Figure 5d) will presumably evolve independently because of sequence differences among diverged monomers. The resulting diverged repeats can be considered as elements of a satDNA library (Fry and Salser, 1977;Meštrović et al, 1998). An additional source of modified repeats can be in gradually degenerated homogeneous arrays predicted to form the final stage in the satDNA life cycle (Figure 5e; Nijman and Lenstra, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copy number of satellite repeats could change mainly by unequal crossing-over events, although other processes, such as replication slippage, rolling-circle replication, conversion-like mechanisms and other unknown mechanisms, could also be involved (reviewed by Charlesworth et al, 1994). Mestrovic et al (1998) demonstrated experimentally, for the first time to our knowledge, some of the postulates of this 'library model'. In coleopteran genera Palorus and Pimelia, it appears that a common ancestor bore the majority of the major satDNA from the present species.…”
Section: Changes In Copy Numbermentioning
confidence: 99%
“…Despite rapid changes in copy numbers, satDNAs are inherited in a linear fashion through generations, and their genomic composition is expected to follow species evolutionary history. Sequence rearrangements such as duplications, insertions, deletions, and inversions within monomers may play a dominant role in the evolution of some satellite sequences (Mravinac and Plohl, 2007), and rearranged monomer variants often follow the principles of the ''library model'', which is based on the differential amplification/contraction of satDNA subfamilies through species/ lineages diversification (Salser et al, 1976;Meštrović et al, 1998). In this model, related species share a ''library'' of conserved satDNA sequence variants, some of which could be amplified into a major satellite due to the evolutionary dynamics of satDNAs.…”
Section: Introductionmentioning
confidence: 99%